Experimental and numerical study of potential infection risks from exposure to bioaerosols in one BSL-3 laboratory. (15th July 2020) - Liu, Zhijian; Zhuang, Wenbin; Hu, Lingfei; Rong, Rui; Li, Jinsong; Ding, Wenjun; Li, Na
Abstract: Laboratory-acquired infections (LAIs) are defined as infections of laboratory staff by exposure to pathogenic microorganisms during an experimental procedure. For a biosafety level-3 (BSL-3) laboratory with a high potential of exposure, reducing risks and threats relevant to LAIs has become a critical concern, especially after the recent outbreak of Novel Coronavirus causing COVID-19 in Wuhan, China. This study aimed to investigate the spatial-temporal characteristics of bioaerosol dispersion and deposition of two kinds of bioaerosols ( Serratia marcescens and phage ΦX174). A combination of laboratory experiment and numerical simulation was adopted to explore bioaerosol removal. Three-dimensional concentration iso-surface mapping in conjunction with flow field analysis was employed to elucidate bioaerosol migration and deposition behavior. The total deposition number and unit area deposition ratio were calculated for different surfaces. The results indicate that bioaerosol concentration remains stable for up to 400 s after release, and that almost 70% of all bioaerosol particles become deposited on the surfaces of walls and equipment. Vortex flow regions and high-concentration regions were determined, and the most severely contaminated surfaces and locations were identified. Our results could provide the scientific basis for controlling the time interval between different experiments and also provide guidelines for a laboratory disinfection routine. Furthermore, future work regarding laboratory layout optimization and high efficiency air distribution for bioaerosol removal in a BSL-3 laboratory should be emphasized. Highlights: Ventilation efficiency of removing two kinds of bioaerosols was quantitatively examined. Removal time for two kinds of bioaerosols in a BSL-3 laboratory was determined. The most seriously contaminated locations in a BSL-3 laboratory were explored. Guidelines for a BSL-3 laboratory follow-up disinfection routine were proposed.